Part 11: Learning Strategies. Issue 4 (2nd October 2019) - Black, Steve; Allen, James D.
ABSTRACT: Educational psychologists have investigated which learning strategies are most effective at promoting long-term learning. The best strategies involve students generating knowledge through sustained engagement. Two of the most valuable strategies are distributing learning over time and testing oneself. Resource-based assignments should require students to submit drafts for formative feedback to promote successive relearning. Students generate understanding through selecting what to pay attention to, organizing what they learn, and integrating it with what they already know. Learning is not easy, students need to experience desirable difficulties to truly learn.